The elephant in the room silence and denial in everyday life - Zerubavel, Eviatar (New York ; Oxford : Oxford University Press, 2006)
This illuminating look at the social roots of silence and denial underscores the social dynamics that keep certain things 'hidden in plain sight'. The author shows how such conspiracies of silence evolve, how people's involvement relate to others and how power differences between people impact on them.
Includes bibliographical references and indexes.
Description based on print version record.
Keywords: Denial (Psychology) -- Social aspects; Avoidance (Psychology) -- Social aspects; Silence; Secrecy; Social psychology